Traditional knowledge and biodiversity conservation: a case study from Byans Valley in Kailash Sacred Landscape, India. Issue 10 (24th August 2018) - Negi, Vikram S.; Pathak, Ravi; Sekar, K. Chandra; Rawal, R.S.; Bhatt, I.D.; Nandi, S.K.; Dhyani, P.P.
Abstract : Ethnobotanical knowledge plays a significant role in plant diversity conservation and the curing of various ailments in remote rural areas of the Indian Himalayan Region (IHR). A total of 53 plant species from 27 families have been documented from the Byans valley and are used traditionally for the treatment of various diseases. Valley inhabitants have maintained a symbiotic relationship between natural resources and their cultural belief system by developing sacred forests/groves which conserve the region's plant diversity pool. Information on sacred natural sites and traditional beliefs was documented in order to understand the environmental and conservationist implications of these rules and practices. The study provides comprehensive information about eroding traditional knowledge and biodiversity conservation practices. This study could be a pilot to strengthen the conservation practices and sustainable utilization of frequently used bioresources by understanding the traditional knowledge system and conservation ethics of tribal communities in the Himalayan region.